2013
DOI: 10.1038/eye.2013.83
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-combination brinzolamide 1%/brimonidine 0.2% vs monotherapy with brinzolamide or brimonidine in patients with open-angle glaucoma or ocular hypertension: results of a pooled analysis of two phase 3 studies

Abstract: PurposeTo describe pooled efficacy and safety data from two phase 3 studies comparing brinzolamide 1%/brimonidine 0.2% fixed combination (BBFC) with its component medications, brinzolamide and brimonidine, in patients with open-angle glaucoma or ocular hypertension.MethodsData were pooled from two nearly identical clinical trials comparing BBFC with its component medications, each given three times daily. The 3-month efficacy outcome was mean intraocular pressure (IOP) at 0800, 1000, 1500, and 1700 hours. Safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 10 publications
1
20
1
Order By: Relevance
“…53 Mean IOP reductions from baseline and percentage change in IOP from baseline were also greater with BBFC (5.7–8.8 mmHg; percentage reduction, 24.1%–34.9%) than with brinzolamide (4.1–6.2 mmHg; percentage reduction, 16.9%–22.6%) or brimonidine (3.5–6.5 mmHg; percentage reduction, 14.3%–25.8%) 53. Similar results were observed in a separate randomized, double-masked Phase III trial with a 3-month safety extension (LS mean IOP at 3 months: BBFC, 17.2–21.1 mmHg; brinzolamide, 20.4–22.0 mmHg, P ≤0.005 versus [vs] BBFC; brimonidine, 18.9–23.2 mmHg, P <0.0001 vs BBFC; Figure 2) and a pooled analysis of both Phase III trials (LS mean IOP at 3 months: BBFC, 17.1–20.8 mmHg; brinzolamide, 20.2–21.8 mmHg, P <0.0001 vs BBFC; brimonidine, 18.8–23.2 mmHg, P <0.0001 vs BBFC) 54,55. Greater reductions in mean IOP with BBFC compared with brinzolamide or brimonidine were observed at week 2 (the first post baseline evaluation day) in both Phase III trials53,54 and continued for up to 6 months (mean reductions from baseline to month 6: 4.9–8.0 mmHg with BBFC, 4.1–5.8 mmHg with brinzolamide, and 3.0–6.3 mmHg with brimonidine) 56.…”
Section: Efficacy Of Bbfcmentioning
confidence: 98%
See 1 more Smart Citation
“…53 Mean IOP reductions from baseline and percentage change in IOP from baseline were also greater with BBFC (5.7–8.8 mmHg; percentage reduction, 24.1%–34.9%) than with brinzolamide (4.1–6.2 mmHg; percentage reduction, 16.9%–22.6%) or brimonidine (3.5–6.5 mmHg; percentage reduction, 14.3%–25.8%) 53. Similar results were observed in a separate randomized, double-masked Phase III trial with a 3-month safety extension (LS mean IOP at 3 months: BBFC, 17.2–21.1 mmHg; brinzolamide, 20.4–22.0 mmHg, P ≤0.005 versus [vs] BBFC; brimonidine, 18.9–23.2 mmHg, P <0.0001 vs BBFC; Figure 2) and a pooled analysis of both Phase III trials (LS mean IOP at 3 months: BBFC, 17.1–20.8 mmHg; brinzolamide, 20.2–21.8 mmHg, P <0.0001 vs BBFC; brimonidine, 18.8–23.2 mmHg, P <0.0001 vs BBFC) 54,55. Greater reductions in mean IOP with BBFC compared with brinzolamide or brimonidine were observed at week 2 (the first post baseline evaluation day) in both Phase III trials53,54 and continued for up to 6 months (mean reductions from baseline to month 6: 4.9–8.0 mmHg with BBFC, 4.1–5.8 mmHg with brinzolamide, and 3.0–6.3 mmHg with brimonidine) 56.…”
Section: Efficacy Of Bbfcmentioning
confidence: 98%
“…For example, a recent systematic review and meta-analysis of randomized trials comparing fixed combinations of prostaglandins and timolol with concomitant administration of both medications showed that the relative risk of hyperemia was lower with the fixed combination than with the unfixed combinations (relative risk, 0.70; 95% confidence interval, 0.43–1.14) 79. In a pooled analysis of two 3-month clinical trials, ocular symptoms that have been associated with preservatives (eg, dry eye and ocular hyperemia) occurred at a similar rate with BBFC (1.4% and 2.1% for dry eye and ocular hyperemia, respectively) compared with individual administration of brinzolamide (0.9% and 0.7%) or brimonidine (1.5% and 3.3%) 55. Although it is possible that punctate keratitis, which was reported in only one of the Phase III trials (0.5%, 0.4%, and 1.4% with BBFC, brinzolamide, and brimonidine, respectively),53 may have contributed to the incidence of these ocular symptoms, this association remains unclear.…”
Section: Safety and Tolerability Of Bbfcmentioning
confidence: 99%
“…In addition, they found that the safety profile is consistent with that of its individual components. 39 This study included data from Katz and colleagues, 40 who demonstrated similar findings.…”
Section: Pharmacologic Intraocular Pressure Loweringmentioning
confidence: 70%
“…Realini and colleagues 39 performed a pooled analysis to compare the effects of treatment with a fixed combination of brinzolamide 1%/brimonidine 0.2% and its component medications on 1350 patients. At the 3-month time point, they found that use of the fixed combination resulted in a statistically significant decrease in IOP compared with either agent alone ( P < 0.0001).…”
Section: Pharmacologic Intraocular Pressure Loweringmentioning
confidence: 99%
“…A combined analysis 28 of two of the phase III trials showed that after 3 months treatment, patients receiving BBFC mean IOP levels were significantly lower than in patients receiving brinzolamide or brimonidine alone (p<0.0001) at four daily time points (08.00, 10.00, 15.00 and 17.00 hours) (see Figure 3). The safety profile of BBFC was shown to be mostly similar to the combined profiles of its two components (brinzolamide and brimonidine).…”
Section: Overview Of European Clinical Studies Of Brinzolamide 1%/brimentioning
confidence: 99%